Tumor suppressor p53 cooperates with SIRT6 to regulate gluconeogenesis by promoting FoxO1 nuclear exclusion - Zhang, Ping; Tu, Bo; Wang, Hua; Cao, Ziyang; Tang, Ming; Zhang, Chaohua; Gu, Bo; Li, Zhiming; Wang, Lina; Yang, Yang; Zhao, Ying; Wang, Haiying; et al. (Proceedings of the National Academy of Sciences - PNAS, 2014)
In mammalian cells, tumor suppressor p53 plays critical roles in the regulation of glucose metabolism, including glycolysis and oxidative phosphorylation, but whether and how p53 also regulates gluconeogenesis is less clear. Here, we report that p53 efficiently down-regulates the expression of phosphoenolpyruvate carboxykinase (PCK1) and glucose-6-phosphatase (G6PC), which encode rate-limiting enzymes in gluconeogenesis. Cell-based assays demonstrate the p53-dependent nuclear exclusion of forkhead box protein O1 (FoxO1), a key transcription factor that mediates activation of PCK1 and G6PC , with consequent alleviation of FoxO1-dependent gluconeogenesis. Further mechanistic studies show that p53 directly activates expression of the NAD ⁺-dependent histone deacetylase sirtuin 6 (SIRT6), whose interaction with FoxO1 leads to FoxO1 deacetylation and export to the cytoplasm. In support of these observations, p53-mediated FoxO1 nuclear exclusion, down-regulation of PCK1 and G6PC expression, and regulation of glucose levels were confirmed in C57BL/J6 mice and in liver-specific Sirt6 conditional knockout mice. Our results provide insights into mechanisms of metabolism-related p53 functions that may be relevant to tumor suppression.